Learning From the Past to Advance the Future: The Adaptation and Resilience of NASA’s Spaceflight Multiteam Systems Across Four Eras of Spaceflight - Pendergraft, Jacob G.; Carter, Dorothy R.; Tseng, Sarena; Landon, Lauren B.; Slack, Kelley J.; Shuffler, Marissa L. (Frontiers in Psychology, 2019)
Many important ‘grand’ challenges—such as sending a team of humans on a voyage to Mars—present superordinate goals that require coordinated efforts across ‘multiteam systems’ comprised of multiple uniquely specialized and interdependent component teams. Given their flexibility and resource capacity, multiteam system structures have great potential to perform adaptively in dynamic contexts. However, these systems may fail to achieve their superordinate goals if constituent members or teams do not adapt their collaboration processes to meet the needs of the changing environment. In this case study of the National Aeronautics and Space Administration (NASA)’s Spaceflight Multiteam Systems (SFMTSs), we aim to support the next era of human spaceflight by considering how the history of manned spaceflight might impact a SFMTS’s ability to respond adaptively to future challenges. We leverage archival documents, including Oral History interviews with NASA personnel, in order to uncover the key attributes and structural features of NASA’s SFMTSs as well as the major goals, critical events, and challenges they have faced over 60 years of operation. The documents reveal three distinct ‘eras’ of spaceflight: (1) Early Exploration, (2) Experimentation, and (3) Habitation, each of which reflected distinct goals, critical events, and challenges. Moreover, we find that within each era, SFMTSs addressed new challenges adaptively by modifying their: (1) technical capabilities; (2) internal collaborative relationships; and/or (3) external partnerships. However, the systems were sometimes slow to implement needed adaptations, and changes were often spurred by initial performance failures. Implications for supporting future SFMTS performance and future directions for MTS theory and research are discussed.